(untitled) (Journal of Oriental Studies, 2016)
This article is based on the questions in the field of comparative literature of Shakarim (1858-1931 AD), the Kazakh nation poet, about anthropology and self- Knowledge, according to the vision of Maulana Jalaluddin Rumi. Also the comparison between the perspectives and worldview of Moulana and Shakarim.